Muhlabje em movimento : reciprocidades burocrático-transinstitucionais na Macia - Bila, Josué Julião (2016)
This enterprise, whose geo-ethnographic impact falls on Muhlabje – one of the neighbourhoods of Macia, southern Mozambique – tries to understand the social relations and political dynamics that move people, community social networks and the Bantu-mozambican authoririties with the municipal bureaucracy and politics, without losing sight of the simultaneously continuous and changing social institutions in that community, which are precedent and in movement with colonial domination and with post-independence Mozambique. The argument also unfolds in capturing the social situations intertwined with each other in a continuous and transdynamic flow, that is, the worship of the ancestors, the ceremony by the Mozambican heroes, the achievements of agriculture, the purchase and sale of a land, the wine donated to the community by politicians and agricultural products donated by the community to politicians and bureaucrats and local feasts are activities-social institutes that cut across the supposed institutional divisions of the impersonal republican bureaucracy and (as opposed to) interpersonal relations (Municipality and communities [neopatrimonialism/clientelism]), the reason why this flow gains the concept of bureaucratictransinstitutional reciprocities.